Nurses' knowledge about obstetric violence (Research, Society and Development, 2024)
Objective: to identify nurses' knowledge about practices considered Obstetric Violence (OV) and their professional performance involving this topic. Method: This is a descriptive, observational, cross-sectional study with a quantitative data approach, carried out online using Forms. The questionnaire included sociodemographic questions and questions about nurses' knowledge. Results: 133 nurses participated in this study, aged between 23 and 58 years. Most of the interviewees work in the Hospital Area (49.6%) and in Primary Care (24.1%). The majority of interviewees know what obstetric violence is and reported the lack of specific training in the context of the service in relation to the topic. A significant proportion of those interviewed (56.4%) revealed that they had witnessed episodes of obstetric violence, perpetrated by other professionals. Conclusion: the research revealed a lack of knowledge and approach to obstetric violence among nurses, from the undergraduate period to professional practice. This finding indicates that professionals are inadequately prepared to deal with this problem, resulting in care provision that lacks quality and effectiveness. This lack of preparation can have serious consequences for the health and well-being of women treated during the gestational period and at the time of birth. Therefore, the need to increase awareness and training of nurses to deal with obstetric violence is evident, in order to guarantee comprehensive and quality care for  pregnant women and women in labor.